Sistem Kewarisan pada Masyarakat Banjar - Muzainah, Gusti; APHA, Journal Manager (Asosiasi Pengajar Hukum Adat (APHA) Indonesia, Fakultas Hukum Universitas Trisakti - Jakarta Barat, Indonesia, 2018)
This study aims to explore the legal values that live in the Banjar community related to the inheritance system. This research is a normative legal research that is examining inheritance legal norms that live and apply in the Banjar community. The results of this study indicate that the inheritance system in the Banjar community is a mixed inheritance system between the individual system and the major system. In the process of inheritance involving Tuan Guru to ask for instructions on the distribution of his inheritance. On the basis of the instructions of Tuan Guru they conduct deliberation or islah. This situation in the Banjar community is to develop religious values into the values of customary law. In the implementation of the distribution of inheritance they prioritize deliberation, if not achieved, it will be forwarded to the religious court.